Mobile phone application : recording on going phone conversations in mobile phones - Chew, Wen Jie. (2013)
Previously, call recording applications were common in mobile operating system such as Symbian. As technology advances rapidly, Symbian is slowly being phased out. Currently, modern mobile operating system starts to take the place of Symbian. The most commonly used mobile operating systems currently are Apple iOS and Google Android.